Effects of probiotics and synbiotic supplementation on antioxidant status: A meta-analysis of randomized clinical trials. (April 2019) - Roshan, Hanieh; Ghaedi, Ehsan; Rahmani, Jamal; Barati, Meisam; Najafi, Marziyeh; Karimzedeh, Mehraneh; Nikpayam, Omid
Summary: Background and aim: Oxidative stress implicated in the pathogenesis of several diseases. Anti-oxidative characteristics of probiotics reported previously. Thus, we aimed to critically investigate the effectiveness of probiotics and synbiotics supplementation on antioxidant biomarkers. Methods: A comprehensive search of Scopus and Medline was performed up to November 2017. All randomized controlled trials (RCT) which evaluate the effect of probiotics or synbiotics on superoxide dismutase (SOD) activity, total antioxidant capacity (TAC) and glutathione (GSH) levels were included. Weighted mean difference (WMD) were pooled using random effect model. Results: Sixteen eligible RCTs with 915 participants were included in present study. Findings showed that probiotics could significantly increase GSH level compared to the control groups ((WMD): 132.36, 95% CI: 27.76, 236.95, P = 0.01). Because of considerable heterogeneity among included the studies, subgroup analyses were conducted. Subgroup analysis revealed that GSH level significantly increased in non-diabetic individuals; the effect size was not significant in diabetic patients. Furthermore, probiotics and synbiotics showed no significant effect on TAC level (WMD: 0.04, 95% CI: −0.07, 0.15, P: 0.50) and SOD activity (WMD: 0.04, 95% CI: −0.06, 0.13, P = 0.43). Conclusion: Probiotics and synbiotics supplementation improve GSH as a biomarkers of antioxidant status in the body. However, additional studies needed for concluding about TAC and SOD activity.